POLITENESS STRATEGIES IN THE TEACHING LEARNING PROCESS IN ENGLISH AS A FOREIGN LANGUAGE (EFL) - Dwi Santoso; Dwi Wahyu Yulianti (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The aim of this study is 1) to investigate the types and the forms of politeness strategies used by the English teachers; and 2) to determine the types and forms of politeness strategies frequently used by the English teachers in EFL based on Brown and Levinson politeness theory. This research is categorized as descriptive qualitative method. the data in this study are utterances uttered by the English teacher in SMA Muhammadiyah 1 Yogyakarta. The researcher applies padan identity method. The researcher triangulated the data by asking at least one person to read the transcription. The conclusion that can be drawn is that there are three types of politeness strategies used by teachers in the EFL teaching and learning process at SMA Muhammadiyah 1 Yogyakarta; namely negative politeness, direct politeness, and positive politeness. Whilst, the forms of politeness strategies used by the teachers in the teaching learning process in EFL at SMA Muhammadiyah 1 Yogyakarta are imperative, declarative, and interrogative. In Addition, it is known that the most type of politeness strategy is negative politeness with a proportion of 41.67 percent and the most form of politeness strategy is imperative sentence with a proportion of 58.33 percent.